An Exploratory Study of Users’ Preference for Different Planting Combinations along Rural Greenways - Natalia Fumagalli (Sustainability, 2020)
The literature highlights the importance of vegetation to enhance the ecological and visual qualities of streets and paths; however, when studies specifically focus on rural greenways they do not consider users’ assessments of the planting design. This exploratory study aims to contribute to this issue. It is hypothesized that planting combinations characterized by greater variety and aesthetic flow may be more preferred and restorative. To this end, four virtual scenarios simulating bikers moving along a greenway at 25 km/h were created to find out the following: first, what kind of planting combination is the most preferred, and second, which planting combination is perceived as the most restorative by bicycle riders. To assess the experience, subjects were administered a questionnaire made up of: (i) the Perceived Restorativeness Scale-11 with additional items to assess compatibility, familiarity, and preference; (ii) a list of physical and aesthetic attributes; and (iii) information on bicycle use. The results show that participants’ preferences were affected by the perception of the scenario’s restorative value, which was not given exclusively by the degree of naturalness, but by the opportunity the greenway offered to engage in social/physical activities. This study shows that preference and restorativeness are not a “simple” matter of quantity of vegetation, but of quality instead, i.e., planting variety. Designers have to consider that the restorative value of greenways is related to the opportunities they offer to engage in physical/social activities.